The Effect Of Performance Appraisal And Reward Towards Healthcare Worker Motivation In Covid-19 Pandemic Situation At Rsud Bandung Kiwari (Journal of Business and Management, 2022)
Abstract: Covid-19 is a pandemic that attacks human respiration. Covid-19 has become a pandemic due to the spread of Covid-19 worldwide which threatens human civilization. Health workers have an important role in suppressing the number of Covid-19 and treat patients exposed to Covid-19.Therefore, health workers need to be noticed because only those who have knowledge about Covid-19. So, by paying attention to Human Resources, Hospitals management can maintain performance and motivation. In this study, the researcher discussed the variables influencing the motivation of healthworkers, namely Performance Appraisal and Rewards. Performance appraisal is an evaluation carried out by comparing current performance with the past and also the objectives of the work. Performance Appraisal can be measured through Relevance, Acceptability, Reliability, Sensitivity, and Practically.Rewards is a reciprocal that is received by someone because they have given energy or contributed to an organization in accordance with the contract specified at the beginning of work. Rewards in this study were measured through Intrinsic and Extrinsic Rewards. The approach taken is a quantitativeapproach with data collection techniques through a questionnaire distributed to 84 respondents. Data processing was carried out using the Multiple Linear Regression Test method through SPSS 25. The results of this study indicate that together Performance Appraisal and Rewards have a positive effecton motivation, Performance Appraisal has a positive effect on motivation, and Rewards has a negative effect on motivation.Keywords: Performance Appraisal, Rewards, Motivation, and Healthcare Worker